Production of Propane and Other Short‐Chain Alkanes by Structure‐Based Engineering of Ligand Specificity in Aldehyde‐Deformylating Oxygenase. Issue 10 (11th June 2013) - Khara, Basile; Menon, Navya; Levy, Colin; Mansell, David; Das, Debasis; Marsh, E. Neil G.; Leys, David; Scrutton, Nigel S.
Abstract : Biocatalytic propane production: structure‐based engineering of aldehyde‐deformylating oxygenase improves specificity for short‐ and medium‐chain‐length aldehydes and enhances the propane generation in whole‐cell biotransformations. This presents new opportunities for developing biocatalytic modules for the production of volatile "drop‐in" biofuels.